THE DETERMINANTS OF SOLVABILITY LEVELS IN SHARIAH LIFE INSURANCE COMPANIES FOR 2014-2018 PERIOD - Herlin Evrilyan; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of this study is to analyze the factors that influence the solvency of the performance of Islamic life insurance companies in the 2014-2018 period. This research uses a quantitative approach with panel data regression analysis method. The data used in this study are secondary data, using a purposive sampling method. The data used by researchers is the financial statements of Islamic life insurance companies in the 2014-2018 period. The population in this journal is the Islamic life insurance industry of 24 companies, while the sample in this journal is 10 samples of Islamic life insurance companies registered with the Financial Services Authority. Partially the findings of this study, which are applied through the variable Company Size and Liquidity Ratios have a significant effect on Solvency, while Claim Expense Ratio, Underwriting Ratio, and Management Cost Ratio have no significant effect on Solvency. Simultaneously Company Size, Liquidity Ratio, Claim Cost Ratio, Underwriting Ratio, and Management Cost Ratio have a significant effect on solvency with a significant level of 0,000 0.05. With the Adjusted R2 value, the result is 0.715554, which means 71.49%, while the remaining 28.51% is influenced by other variables outside this study.Keyword: Islamic Life Insurance, solvency, Risk Based Capital, Islamic InsuranceREFFERENCESAl Arif, M Nur Rianto. (2015.) Pengantar Ekonomi Syariah: Teori dan Praktek. Bandung: CV Pustaka SetiaAscarya. (2015). Akad & Produk Bank Syariah. Jakarta: Raja Grafindo PersadaCahyadi, Thalis Noor. (2012). Baitul Maal Wat Tamwil Legalitas Dan Pengawasannya. Jurnal Ekonomi Syariah Indonesia, Vol. 11, No. 2Dewan Syariah Nasional-Majelis Ulama Indonesia. 2000. Fatwa DSN-MUI No. 04/DSN-MUI/IV/2000 Tentang Murabahah. (Online). https://dsnmui.or.id/category/fatwa/page/11/, diakses 30 September 2018.Imama, Lely Shofa. (2014).  Konsep Dan Implementasi Murabahah pada Produk Pembiayaan Bank Syariah. Iqtisodia, vol. 1, no. 2Imaniyati, Neni Sri. (2010). Aspek-aspek Hukum BMT (Baitul Maal Wa Tamwil). Bandung: PT Citra Aditya BaktiKuncoro, Amin dan Husnurrosyidah. (2017). Kinerja Lembaga Keuangan Mikro Syariah Dan Upaya Untuk Mempertahankan Eksistensi Perilaku Masyarakat Pedesaan. Jurnal Analisa Akuntansi dan Perpajakan, Vol. 1, No. 1Prabowo, Bagya Agung. 2009. Konsep Akad Murabahah pada Perbankan Syariah (Analisa Kritis terhadap Aplikasi Konsep Akad Murabahah di Indonesia dan Malaysia. Jurnal Hukum, vol. 16, no. 1Rivai, Veithzal dkk. 2010. Islamic Financial Management. Bogor: Penerbit Ghalia IndonesiaSupriyanto dkk. (2018). Islam and Local Wisdom: Religious Expression In Southeast Asia. Sleman: DeepublishSyamsuir. (2015). Lembaga Keuangan Islam Non Bank. Jurnal Islamika, Vol. 15, No. 1Salam, Abdul Qodir. Teori Dharurah dan Pengaruhnya terhadap Perubahan Status Hukum. (Online). http://pcinu-mesir.tripod.com/ilmiah/jurnal/isjurnal/nuansa/Jan96/6.htm diakses 09 Januari 2019Waluyo, Bambang. (2016). Implementasi Pembiayaan Mudharabah pada Bank Syariah untuk Merealisasikan Tujuan Ekonomi Islam. Jurnal Ekonomi dan Bisnis Islam, vol. 2, no. 2Yin, Robert K. (2015). Studi Kasus: Desain & Metode. Jakarta: Rajwali Pers